Macrophage autophagy regulates mitochondria‐mediated apoptosis and inhibits necrotic core formation in vulnerable plaques. Issue 1 (29th October 2019) - Xiao, Qingqing; Che, Xinyu; Cai, Bin; Tao, Zhenyu; Zhang, Hengyuan; Shao, Qin; Pu, Jun
Abstract: The vulnerable plaque is a key distinguishing feature of atherosclerotic lesions that can cause acute atherothrombotic vascular disease. This study was designed to explore the effect of autophagy on mitochondria‐mediated macrophage apoptosis and vulnerable plaques. Here, we generated the mouse model of vulnerable carotid plaque in ApoE −/− mice. Application of ApoE −/− mice with rapamycin (an autophagy inducer) inhibited necrotic core formation in vulnerable plaques by decreasing macrophage apoptosis. However, 3‐methyladenine (an autophagy inhibitor) promoted plaque vulnerability through deteriorating these indexes. To further explore the mechanism of autophagy on macrophage apoptosis, we used macrophage apoptosis model in vitro and found that 7‐ketocholesterol (7‐KC, one of the primary oxysterols in oxLDL) caused macrophage apoptosis with concomitant impairment of mitochondria, characterized by the impairment of mitochondrial ultrastructure, cytochrome c release, mitochondrial potential dissipation, mitochondrial fragmentation, excessive ROS generation and both caspase‐9 and caspase‐3 activation. Interestingly, such mitochondrial apoptotic responses were ameliorated by autophagy activator, but exacerbated by autophagy inhibitor. Finally, we found that MAPK‐NF‐κB signalling pathway was involved in autophagy modulation of 7‐KC–induced macrophage apoptosis. So, we provide strong evidence for the potential therapeutic benefit of macrophage autophagy in regulating mitochondria‐mediated apoptosis and inhibiting necrotic core formation in vulnerable plaques.